An Approach for Computed Tomography Images Enhancement - Georgieva, V. M. (Elektronika ir Elektrotechnika, 2010)
A new approach for computed tomography (CT) images enhancement is presented. It consists of the following stages for image processing: selecting of the region of interest (ROI), contrast increasing by gamma correction, morphological processing of the selected ROI and noise reduction on the base of 2D wavelet packet transformations. Treatment on the base of investigation on the most suitable morphological operators and on optimization of some parameters of the wavelet transformations was the most suitable algorithm. The 74 aim is to improve the quality of the diagnostic computed tomography images. Some results of the experiments are presented, which were made by computer simulation in MATLAB environment. Ill. 8, bibl. 7 (in English; summaries in English, Russian and Lithuanian).